2015
DOI: 10.1038/srep16772
|View full text |Cite
|
Sign up to set email alerts
|

Role of different scattering mechanisms on the temperature dependence of transport in graphene

Abstract: Detailed experimental and theoretical studies of the temperature dependence of the effect of different scattering mechanisms on electrical transport properties of graphene devices are presented. We find that for high mobility devices the transport properties are mainly governed by completely screened short range impurity scattering. On the other hand, for the low mobility devices transport properties are determined by both types of scattering potentials - long range due to ionized impurities and short range du… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 38 publications
2
16
1
Order By: Relevance
“…[134] Also, as the mechanical test is performed in an environment containing a high-energy electron beam, attention must be paid on how electron beam irradiation (EBI) would affect the mechanical properties of NWs. [83,135] Thermal effect and knock-on effect from energetic electrons in TEM or SEM may contribute to NW specimens damage. [136] Thermal effect induced by energetic electrons is difficult to quantify, however recent studies have revealed that the temperature increase of a NW sample during a normal TEM imaging process is far below 100 °C.…”
Section: The Challenges Of Em Testsmentioning
confidence: 99%
“…[134] Also, as the mechanical test is performed in an environment containing a high-energy electron beam, attention must be paid on how electron beam irradiation (EBI) would affect the mechanical properties of NWs. [83,135] Thermal effect and knock-on effect from energetic electrons in TEM or SEM may contribute to NW specimens damage. [136] Thermal effect induced by energetic electrons is difficult to quantify, however recent studies have revealed that the temperature increase of a NW sample during a normal TEM imaging process is far below 100 °C.…”
Section: The Challenges Of Em Testsmentioning
confidence: 99%
“…It is believed that the transport properties of graphene are mainly defined by carrier scattering on charged impurities . However, in pure samples short‐range scattering can play an important role . It was shown that the type of the scattering can be recognized from the shape of the conductivity dependence measured as a function of the back gate voltage.…”
Section: Introductionmentioning
confidence: 99%
“…5,[7][8][9] The disadvantage of these methods is, that the conditions under which the mobility is obtained are not the same as for a transistor structure. Alternatively, a commonly accepted experimental method for finding mobility values by direct measurements on G-FETs is to fit a simplified expression for the drain resistance to drain resistance--gate voltage characteristics [10][11][12][13][14] R ¼ R c þ ðL=WÞðqlÞ À1 ððn 0 2 0 þ ðCðV g À V Dirac Þ=qÞ 2 Þ À1=2 :…”
Section: Introductionmentioning
confidence: 99%